2022
DOI: 10.1108/jiabr-02-2021-0060
|View full text |Cite
|
Sign up to set email alerts
|

Shariah vs non-shariah IPO underpricing: evidence from Indonesia Stock Exchange

Abstract: Purpose This study aims to investigate the effect of shariah status on initial public offering (IPO) underpricing, long-term performance and relationship between short-term and long-term IPO performance, and attempt to gain an insight into the nature of shariah IPO underpricing: a signal or an overreaction. Design/methodology/approach This study uses IPOs during 1990–2018 from Indonesia. This study uses clustered regressions to address clustering phenomenon in IPO. To investigate long-term performance, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The highest underperformance occurred in the highest initial return group, which showed worse long-term performance than IPO companies with lower initial returns in the Mauritius capital market from 1989 to 2010. Furthermore, research with the case study of the Indonesia Stock Exchange (Adrian et al, 2019) found the result that the more, more significant the initial return rate during the IPO of stock, the worse the long-term performance of the company, while according to (Hanafi & Hanafi, 2022) more specifically found that there was a negative relationship initial return and longterm performance for Islamic and non-Sharia IPOs in Indonesia. , this study uses IPOs during 1990-2018 from Indonesia.…”
Section: The Effect Of Initial Return On the Long-term Performance Of...mentioning
confidence: 99%
“…The highest underperformance occurred in the highest initial return group, which showed worse long-term performance than IPO companies with lower initial returns in the Mauritius capital market from 1989 to 2010. Furthermore, research with the case study of the Indonesia Stock Exchange (Adrian et al, 2019) found the result that the more, more significant the initial return rate during the IPO of stock, the worse the long-term performance of the company, while according to (Hanafi & Hanafi, 2022) more specifically found that there was a negative relationship initial return and longterm performance for Islamic and non-Sharia IPOs in Indonesia. , this study uses IPOs during 1990-2018 from Indonesia.…”
Section: The Effect Of Initial Return On the Long-term Performance Of...mentioning
confidence: 99%
“…Sebaliknya, sebagian besar negara Asia, menggunakan mekanisme harga tetap saat menerbitkan IPO [4]. Dalam menetapkan harga penawaran IPO dengan mekanisme harga tetap, penjamin emisi bersama emiten menentukan harga tanpa memperoleh informasi dari calon investor [5].…”
Section: Pendahuluanunclassified
“…Through their initial public offering (IPO) in the primary market, they receive fresh funds to strengthen their core capital (Sari, 2022) and expand their business (Hutauruk, 2023). After the first-day IPO, the banking stock price is always higher than the offering price (Hanafi & Hanafi, 2022), set by the deal between the bank as the share issuer and the underwriter (Widyawati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%